2012
DOI: 10.1371/journal.ppat.1002662
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus LMP2A Reduces Hyperactivation Induced by LMP1 to Restore Normal B Cell Phenotype in Transgenic Mice

Abstract: Epstein-Barr virus (EBV) latently infects most of the human population and is strongly associated with lymphoproliferative disorders. EBV encodes several latency proteins affecting B cell proliferation and survival, including latent membrane protein 2A (LMP2A) and the EBV oncoprotein LMP1. LMP1 and LMP2A signaling mimics CD40 and BCR signaling, respectively, and has been proposed to alter B cell functions including the ability of latently-infected B cells to access and transit the germinal center. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 61 publications
3
30
1
Order By: Relevance
“…Here LMP2A appeared to negatively modulate the function of LMP1, rescuing the loss of GC B cells caused by LMP1 expression. A clear difference with respect to our previous and present work is the presence of large numbers of LMP-expressing cells in the mice analyzed by Longnecker and colleagues (32), suggesting that the levels of LMP1 expression were insufficient to induce T-cell immune surveillance as it is seen in the present mouse model and in human EBV infection. Indeed, there is evidence that LMP2A augments LMP1 signaling in human EBVinfected cells (33).…”
Section: Discussioncontrasting
confidence: 99%
“…Here LMP2A appeared to negatively modulate the function of LMP1, rescuing the loss of GC B cells caused by LMP1 expression. A clear difference with respect to our previous and present work is the presence of large numbers of LMP-expressing cells in the mice analyzed by Longnecker and colleagues (32), suggesting that the levels of LMP1 expression were insufficient to induce T-cell immune surveillance as it is seen in the present mouse model and in human EBV infection. Indeed, there is evidence that LMP2A augments LMP1 signaling in human EBVinfected cells (33).…”
Section: Discussioncontrasting
confidence: 99%
“…Consistent with this observation, LMP2A coexpression reversed LMP1-induced B-cell hyperactivation phenotypes in a murine model (22). Pathways suppressed by LMP2A expression included apoptosis, Toll-like receptor signaling, B-cell receptor signaling, and the TNFα/ NF-κB pathway (Table S3).…”
Section: Discussionsupporting
confidence: 68%
“…However, B-lineage-specific expression of LMP1 inhibits GC formation (20) or causes B-cell ablation through immune surveillance (21). LMP2A does not affect affinity maturation of B cells in GCs when expressed in B cells of a transgenic mouse line (22). Constitutive expression in transgenic mice used in these previous studies may be inappropriate for studying the influence of infection-induced virus proteins on B-cell differentiation, particularly in GCs.…”
mentioning
confidence: 99%
“…In classic studies, LMP1 was found to transform rodent fibroblasts, to drive epithelial xenograft tumor formation (7,66), and to accelerate B-cell lymphomagenesis (9). When expressed alone or together with LMP2A from an early stage of B-cell development, immune surveillance prevents lymphomagenesis (8,67). Notably, the loss of T-cell surveillance results in LMP1-driven fatal lymphoproliferative disease within 60 days (8).…”
Section: Mouse Models Of Lmp1 Lymphomagenesismentioning
confidence: 99%